Old Town, Yellowknife, NT -- photograph - Seale, Linda N. (2012)
View of Old Town, Yellowknife, from the ice on Yellowknife Bay. Pilot's Monument at the top of the hill commemorates early bush pilots and also has a flashing light that warns if a small plane is about to land or take off in the channel between Old Town and Jolliffe Island. Photograph taken March 2012